Integrated orofacial therapy in chronic rhinosinusitis management for children with sleep bruxism - Haryono Utomo (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: The prevalence of rhinosinusitis was 20% in ambulatory patients and was mostly affected by viral infections and allergy. If conservative treatments of rhinosinusitis failed, surgical procedure is an alternative choice. Previous case report revealed that the rhinosinusitis symptoms were successfully relieved by the "assisted drainage" therapy only. Nevertheless, this therapy was less successful in children with sleep bruxism (SB). Purpose: To report an integrated orofacial therapy for management of rhinosinusitis children with sleep bruxism (SB) which consisted of the assisted drainage, night-guard and masseter muscle massage therapies. Case: Two boys who suffered from rhinosinusitis with bruxism were unsuccessfully treated with conventional treatment. Case management: Patients was subjected to the assisted drainage therapy that was scaling and root planning combined with gingival massage, and masseter muscle massage; night guard was worn in night sleep. They successfully relieved the rhinosinusitis symptoms. Conclusion: Based on the successful result, this integrated therapy could be suggested as an adjuvant in rhinosinusitis management.Latar belakang: Prevalensi rinosinusitis adalah 20% pasien rawat jalan dan umumnya disebabkan oleh infeksi virus dan alergi. Apabila terapi konservatif rinosinusitis mengalami kegagalan maka pilihan terakhir adalah operasi. Pada laporan kasus yang ada telah terjadi perbaikan gejala rinosinusitis setelah dilakukan terapi “assisted drainage” saja. Akan tetapi, terapi ini kurang berhasil pada anak dengan sleep bruxism (SB). Tujuan: Melaporkan suatu terapi orofasial terintegrasi untuk tatalaksana rinosinusitis pada anak dengan sleep bruxism (SB) yang terdiri dari terapi assisted drainage, night guard dan masase otot masseter. Kasus: Dua anak laki-laki yang menderita rinosinusitis dengan bruxism telah mengalami kegagalan pada perawatan konsvensional. Tatalaksana kasus: Pasien dilakukan terapi assisted drainage yang adalah scaling dan root planning yang dikombinasikan dengan masase gingiva dan masase otot masseter; sedangkan nightguard dipakai saat tidur malam. Terapi ini berhasil mengurangi gejala rinosinusitis. Kesimpulan: Berdasarkan keberhasilan terapi, terapi terintegrasi ini dapat digunakan sebagai ajuvan dalam tatalaksana sinusitis.